Reactogenicity of yellow fever vaccines in a randomized, placebo-controlled trial Reatogenicidade de vacinas contra febre amarela em estudo randomizado, controlado com placebo - Luiz Antonio Bastos Camacho; Savitri Gomes de Aguiar; Marcos da Silva Freire; Maria da Luz Fernandes Leal; Jussara Pereira do Nascimento; Takumi Iguchi; José Azevedo Lozana; Roberto Henrique Guedes Farias (Universidade de São Paulo, 2005)
OBJECTIVE: To compare the reactogenicity of three yellow fever (YF) vaccines from WHO-17D and Brazilian 17DD substrains (different seed-lots) and placebo. METHODS: The study involved 1,087 adults eligible for YF vaccine in Rio de Janeiro, Brazil. Vaccines produced by Bio-Manguinhos, Fiocruz (Rio de Janeiro, Brazil) were administered ("day 0") following standardized procedures adapted to allow blinding and blocked randomization of participants to coded vaccine types. Adverse events after immunization were ascertained in an interview and in diary forms filled in by each participant. Liver enzymes were measured on days 0, 4-20 and 30 of the study. Viremia levels were measured on days 4 to 20 of follow-up. The immune response was verified through serologic tests. RESULTS: Participants were mostly young males. The seroconversion rate was above 98% among those seronegative before immunization. Compared to placebo, the excess risk of any local adverse events ranged from 0.9% to 2.5%, whereas for any systemic adverse events it ranged from 3.5% to 7.4% across vaccine groups. The excess risk of events leading to search for medical care or to interruption of work activities ranged from 2% to 4.5%. Viremia was detected in 3%-6% of vaccinees up to 10 days after vaccination. Variations in liver enzyme levels after vaccination were similar in placebo and vaccine recipients. CONCLUSIONS: The frequency of adverse events post-immunization against YF, accounting for the background occurrence of nonspecific signs and symptoms, was shown for the first time to be similar for vaccines from 17D and 17DD substrains. The data also provided evidence against viscerotropism of vaccine virus. OBJETIVO: Comparar a reatogenicidade de três vacinas contra a febre amarela (FA) das sub-cepas WHO-17D e 17DD (diferentes lotes-semente), e placebo. MÉTODOS: Foram recrutados 1.087 adultos elegíveis para vacinação contra FA no Rio de Janeiro, RJ, Brasil. Vacinas produzidas por Bio-Manguinhos, Fiocruz (Rio de Janeiro, RJ) foram administradas ("dia zero") seguindo procedimentos adaptados para alocação randômica em blocos e "cega" para o tipo de vacina. Eventos adversos pós-vacinação foram registrados em questionários e diários preenchidos pelos participantes. Enzimas hepáticas foram medidas nos dias 0, 4-20 e 30 do estudo. A viremia foi medida nos dias 4-20. A resposta imune foi verificada em testes sorológicos nos dias 0 e 30. RESULTADOS: Os participantes eram predominantemente homens jovens. A taxa de soroconversão foi superior a 98% no grupo soronegativo antes da vacinação. Comparado ao placebo, a diferença de risco de eventos adversos locais variou de 0,9% a 2,5%, e de 3,5% a 7,4% para eventos adversos sistêmicos nos grupos vacinados. A diferença de risco desses eventos com assistência médica e/ou falta ao trabalho variou de 2,0% a 4,5%. Viremia foi detectada em 3% a 6% dos vacinados até 10 dias após a vacinação. As variações nos níveis de enzimas hepáticas pós-vacinação foram semelhantes nos grupos vacinados e placebo. CONCLUSÕES: Foi demonstrada pela primeira vez a semelhança do perfil de reatogenicidade das vacinas contra FA das cepas 17D e 17DD, comparados entre si e com placebo. As variações das enzimas hepáticas constituem evidência contra o potencial de viscerotropismo do vírus vacinal.